Hubungan Kekerabatan Fenetik Sembilan Spesies Anggota Myrtaceae Berdasarkan Morfologi dan Karakter Anatomis Daun - Rizanda, Nabila Hasna (Berkala Ilmiah Biologi, 2024)
Myrtaceae family is well-known for its beneficial essential oils as anti-inflammatory and anti-bacterial. There are more than 30 genera within Myrtaceae family in Indonesia, and they show high morphological variations. This study aims to determine the phenetic relationship of nine species of Myrtacee based on the morphology and leaf anatomical characters. The phenetic relationship was analyzed based on morphology and leaf anatomical characters. Plant samples were collected from the Wanagama and Imogiri Forest areas, Special Region of Yogyakarta. Sample identification resulted in the recognition of nine species belong to the genera Eucalyptus, Syzygium, Eugenia, Psidium, and Melaleuca. Phenetic relationship analysis was carried out by cluster analysis of 30 morphological and leaf anatomical characters using Euclidean distance and the UPGMA clustering method. The resulted dendogram showed the formation of two clusters. The first cluster consists of species from the genus Eucalyptus, while the second cluster consists of species from the genera Syzygium, Eugenia, Psidium, and Melaleuca. The results of principal component analysis showed that bark structure, the type of calcium oxalate crystals, and leaf apex were a three characters with major role in the grouping of species and genera. The results of this study confirm the role of morphological and anatomical characters as taxonomic evidence for the classification of species and genera in Myrtaceae family.